2021
DOI: 10.1177/1868103421989712
|View full text |Cite
|
Sign up to set email alerts
|

Women Who Persist: Pathways to Power in Eastern Indonesia

Abstract: In contrast to accounts that explain increases in women’s political representation by reference to structural and institutional factors, this article draws attention to the agency of women candidates. The number of women elected in the Eastern Indonesian province of East Nusa Tenggara ( Nusa Tenggara Timur, NTT) increased markedly in 2019. To explain this increase, this article highlights the remarkable persistence of women candidates, many of whom succeeded in 2019 only after competing in multiple prior elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…In line with other research explaining findings related to the existence of obstacles to women's political participation in Indonesia, including understanding religion (Fattore et al, 2010), the strong patriarchal culture of society (Dzuhayatin, 2020;Prajuli et al, 2021), structural and institutional factors that confront with women's domestic duties (Bayo, 2021;Christoff et al, 2017), even the blurred understanding of all parties regarding gender bias which still often occurs both in government and society (Badruddin et al, 2019), lack of financial support and political support ( Adnan & Amri, 2021), where even political parties only view women's involvement as a formality in fulfilling the women's quota policy (Angin & Purnomo, 2022) as well as the lack of access to information, resources and political education received by women's groups (Yanti et al, n.d.;Yumasdaleni et al, 2022) On the other hand, in several articles it was also found that there are political parties that have not provided sufficient portions for women's involvement (Rofhani & Fuad, 2021;Savirani et al, 2021). Apart from that, it also needs to be acknowledged that there is still a gender gap in knowledge and preferences.…”
Section: The Stagnation Of Women's Electability: Priorities or Policy...supporting
confidence: 84%
“…In line with other research explaining findings related to the existence of obstacles to women's political participation in Indonesia, including understanding religion (Fattore et al, 2010), the strong patriarchal culture of society (Dzuhayatin, 2020;Prajuli et al, 2021), structural and institutional factors that confront with women's domestic duties (Bayo, 2021;Christoff et al, 2017), even the blurred understanding of all parties regarding gender bias which still often occurs both in government and society (Badruddin et al, 2019), lack of financial support and political support ( Adnan & Amri, 2021), where even political parties only view women's involvement as a formality in fulfilling the women's quota policy (Angin & Purnomo, 2022) as well as the lack of access to information, resources and political education received by women's groups (Yanti et al, n.d.;Yumasdaleni et al, 2022) On the other hand, in several articles it was also found that there are political parties that have not provided sufficient portions for women's involvement (Rofhani & Fuad, 2021;Savirani et al, 2021). Apart from that, it also needs to be acknowledged that there is still a gender gap in knowledge and preferences.…”
Section: The Stagnation Of Women's Electability: Priorities or Policy...supporting
confidence: 84%
“…The common belief among the Indonesian public is that elections are unavoidably expensive, yet recent research demonstrates they are not. A special issue on women's experiences in the 2019 election provides evidence that drawing upon women's networks-homosocial capitalis an effective strategy for women candidates that allows them to overcome structural barriers to election, including money politics (Aspinall et al 2021;Mahsun et al 2021;Novadona Bayo 2021). Our research too shows that money politics is not an insurmountable barrier for candidates who do not have access to large amounts of funding.…”
mentioning
confidence: 67%
“…The dearth of female representatives in Indonesia has been the focus of several studies (Bessell 2010;Hillman 2017Hillman , 2018Perdana and Hillman 2020;Prihatini 2018Prihatini , 2019b; several scholars have also analyzed the pathways of women who have managed to break through the barriers and win elective office, sometimes by using connections to male elites, sometimes by mobilizing support from grassroots or religious women's networks (Aspinall, White, and Savirani 2021;Bayo 2021;Choi 2018;Kabullah and Fajri 2021;Mahsun, Elizabeth, and Mufrikhah 2021;Prihatini 2019c;Shair-Rosenfield 2012;Wardani and Subekti 2021). Much of this literature focuses on supply and demand barriers associated with political recruitment, highlighting obstacles such as reluctance by political parties to endorse strong female candidates (e.g., Hillman 2018, 331-32;Wardani and Subekti 2021) and the limited material resources and political networks accessible to female candidates compared to their male competitors (Hillman 2018, 328-31).…”
Section: The Indonesian Casementioning
confidence: 99%